Hubungan Pengetahuan dan Sikap terhadap Perilaku Seks Bebas pada Remaja di SMK Negeri 9 Pangkep Tahun 2023 - Sri Ayu Nata; Nurdalifah Nurdalifah; Nopiyanti Nopiyanti; Rusmawati Rusmawati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Free sex behavior is any behavior that is driven by the desire to have free sex either with the opposite sex or the same sex. This behavior ranges from feelings of attraction to dating, courtship and sexual relations. The research objective was to determine the relationship between knowledge and attitudes towards free sex behavior in adolescents at SMK Negeri 9 Pangkep in 2023. This type of research is quantitative research with analytical surveys and surveys (Cross Sectional). Cross sectional is a technique of collecting data, observing and sampling simultaneously to analyze the dynamics of correlated risk variables and their consequences, with a sample of 89 respondents at SMK Negeri 9 Pangkep in 2023. The relationship between variables was tested using the Chi-Square test with a significant value ( a = 0.05). The results showed that there was a significant relationship between knowledge ρ = 0.000 and attitude ρ = 0.000 towards free sex behavior in adolescents at SMK Negeri 9 Pangkep in 2023.